The Use of HOTS-Oriented Project-Based Learning Model to Improve Grade XI Students’ English Speaking Performance tt SMAN 8 Bengkulu City - Rinti Safetri; Ira Maisarah (LPPM Universitas PGRI Semarang, 2026)
This study examined changes in Grade XI students’ English speaking performance following participation in HOTS-oriented Project-Based Learning (PjBL) activities at SMAN 8 Bengkulu City. This study employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The participants were 32 Grade XI students. Data were collected through oral presentation tests administered before and after the intervention. Students’ speaking performance was assessed using a rubric consisting of five components: pronunciation, fluency, vocabulary, grammar, and comprehension. The instrument validity was evaluated through expert assessment, while reliability was examined using inter-rater reliability analysis with a coefficient of 0.87. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, paired sample t-test, Cohen’s d effect size, and normalized gain analysis. The findings showed that students’ mean speaking scores increased from 58.44 in the pretest to 81.31 in the posttest, with a mean gain of 22.87 points. The paired sample t-test revealed a significant difference between pretest and posttest scores, t(31)=61.000, p<0.001. The effect size analysis indicated a very large standardized difference (Cohen’s d=10.783), while the normalized gain score was 0.55, indicating moderate improvement. Descriptive analysis showed improvements across all speaking components, with fluency demonstrating the highest gain. These findings suggest that HOTS-oriented PjBL provided opportunities for students to engage in contextual communication through problem analysis, idea development, project presentation, and reflection. However, the findings should be interpreted cautiously due to the limitations of the one-group design.